STUDY LITERATUR REVIEW : PENDEKATAN DAN TANTANGAN DALAM PERENCANAAN STRATEGIS UNTUK PEMBANGUNAN BERKELANJUTAN - Ira Mieke Andariyani; Dewi Martha; Alfi Syukria (Jurnal Ekonomi Bisnis Kompetif, 2025)
Sustainable development requires development planning that integrates economic, social, and environmental dimensions while remaining adaptive to future uncertainties. Strategic planning plays a crucial role in guiding long-term policies to address challenges such as climate change, environmental degradation, and global development dynamics. This study aims to examine key approaches and challenges in strategic planning for sustainable development using a systematic literature review (SLR). The review applies the PRISMA framework to academic publications from 2011–2025 obtained from Scopus, Web of Science, ScienceDirect, Google Scholar, and ProQuest. The findings indicate that strategic planning approaches have evolved in a multidisciplinary manner, including quantitative SWOT analysis, spatial modeling and GIS, stochastic optimization, nature-based solutions, and information technology integration. However, their implementation faces persistent challenges, such as limited institutional capacity, weak cross-sectoral coordination, data constraints, low public participation, and environmental and climate uncertainty. This study highlights the need for adaptive, evidence-based, and collaborative strategic planning to effectively support sustainable development goals.